Artificial Intelligence Hallucination in EFL Academic Writing: A Systematic Literature Review and Future Research Agenda for Islamic Higher Education - Suhono Suhono (CV. Creative Tugu Pena, 2026)
The rapid adoption of Generative Artificial Intelligence (GenAI) tools such as ChatGPT, Gemini, Claude, and Copilot has transformed academic writing practices in higher education, particularly in English as a Foreign Language (EFL) contexts. While these technologies offer substantial benefits for idea generation, language support, and writing development, they also introduce significant challenges related to Artificial Intelligence (AI) hallucination. Despite the increasing scholarly attention to AI in education, existing research on AI hallucination remains fragmented across disciplines and lacks a comprehensive synthesis that addresses its implications for EFL academic writing and Islamic Higher Education. This study aims to systematically review the existing literature on AI hallucination in EFL academic writing and develop a future research agenda relevant to Islamic Higher Education. Employing a Systematic Literature Review (SLR) design, the study follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA 2020) guidelines to identify, screen, evaluate, and synthesize relevant studies published in internationally recognized databases. The result revealed that the key patterns concerning factual hallucination, citation hallucination, conceptual hallucination, and interpretative hallucination, as well as the challenges these phenomena pose to academic integrity and knowledge construction. Furthermore, the synthesis highlights the growing importance of Critical AI Literacy as a pedagogical approach for enabling students to evaluate, verify, and responsibly utilize AI-generated information. From the perspective of Islamic Higher Education, the study argues that Islamic epistemological principles, particularly tabayyun (information verification), amanah (trustworthiness), and intellectual responsibility, provide a valuable conceptual foundation for mitigating the risks associated with AI hallucination. This study contributes to the emerging scholarship on AI-assisted learning by offering an integrated understanding of AI hallucination in EFL academic writing and proposing a future research agenda that bridges Critical AI Literacy, academic integrity, and Islamic educational values.